2020
DOI: 10.1007/s00431-020-03620-9
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dense, low-volume paediatric oral nutritional supplements improve total nutrient intake and increase growth in paediatric patients requiring nutritional support: results of a randomised controlled pilot trial

Abstract: Children with or at risk of faltering growth require nutritional support and are often prescribed oral nutritional supplements (ONS). This randomised controlled trial investigated the effects of energy-dense paediatric ONS (2.4 kcal/ml, 125 ml: cONS) versus 1.5 kcal/ml, 200 ml ONS (sONS) in community-based paediatric patients requiring oral nutritional support. Fifty-one patients (mean age 5.8 years (SD 3)) with faltering growth and/or requiring ONS to meet their nutritional requirements were randomised to cON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Energy-dense oral nutrition supplements should be offered to children not meeting nutritional needs with an oral diet alone. In a randomized controlled trial of children with faltering growth, energy-dense oral nutrition supplementation has been shown to result in significantly higher energy intake compared to lower-density oral nutrition supplements [53]. Furthermore, the use of energy-dense formula in critically ill adults has been shown to meet nutritional needs sooner due to the ability to achieve goal energy needs in less time, allowing for meeting nutritional goals despite procedural disruptions [54].…”
Section: Clinical Practice Recommendations and Rationalementioning
confidence: 99%
“…Energy-dense oral nutrition supplements should be offered to children not meeting nutritional needs with an oral diet alone. In a randomized controlled trial of children with faltering growth, energy-dense oral nutrition supplementation has been shown to result in significantly higher energy intake compared to lower-density oral nutrition supplements [53]. Furthermore, the use of energy-dense formula in critically ill adults has been shown to meet nutritional needs sooner due to the ability to achieve goal energy needs in less time, allowing for meeting nutritional goals despite procedural disruptions [54].…”
Section: Clinical Practice Recommendations and Rationalementioning
confidence: 99%
“…Although this study involved a short period of time, the results are in line with those found in the sequence B of our research (79% vs. 84%). Another study investigating the effects of energy-dense ONS vs. standard ONS of 1.5 kcal/mL in pediatric population, showed similar results with a greater proportion of patients with high compliance in the group receiving the energy-dense ONS ( 15 ). The authors attribute this to the good acceptability, and higher energy and nutrient density of the formula in a smaller volume.…”
Section: Discussionmentioning
confidence: 79%
“…The majority of patients did not report any GI symptoms throughout the study; however, some patients reported GI symptoms with various levels of severity whilst on the KD during the control period, at a similar level to that report in both randomized controlled trials 13 and uncontrolled studies 12 of the KD, and in other studies of the use of nutritional support in various disease areas. [20][21][22][23] More absent symptoms were reported during the intervention period with the use of the 2.5:1 ratio feed compared to the control period. This is encouraging and was predominantly driven by the lower incidence of mild and moderate GI side effects.…”
Section: Discussionmentioning
confidence: 99%